Decision space and participation of primary healthcare facility managers in the Ideal Clinic Realisation and Maintenance programme in two South African provinces. Issue 3 (23rd December 2019) - Muthathi, Immaculate Sabelile; Levin, Jonathan; Rispel, Laetitia C
Abstract: In South Africa, the introduction of a national health insurance (NHI) system is the most prominent health sector reform planned to achieve universal health coverage in the country. Primary health care (PHC) is the foundation of the proposed NHI system. This study draws on policy implementation theory and Bossert's notion of decision space to analyse PHC facility managers' decision space and their participation in the implementation of the Ideal Clinic Realisation and Maintenance (ICRM) programme. We conducted a cross-sectional survey among 127 PHC facility managers in two districts in Gauteng and Mpumalanga provinces. A self-administered questionnaire elicited socio-demographic information, the PHC managers' participation in the conceptualization and implementation of the ICRM programme, their decision space and an optional open-ended question for further comments. We obtained a 100% response rate. The study found that PHC facility managers reported lack of involvement in the conceptualization of the ICRM programme, high levels of participation in implementation [mean score 5.77 (SD ±0.90), and overall decision space mean score of 2.54 (SD ±0.34)]. However, 17 and 21% of participants reported narrow decision space on the critical areas of the availability of essential medicines and on basic resuscitation equipment respectively. The qualitative data revealed the unintended negative consequences of striving for 'ideal clinic status', namely that of creating an illusion of compliance with the ICRM standards. The study findings suggest the need for greater investment in the health workforce, special efforts to involve frontline managers and staff in health reforms, as well as provision of adequate resources, and an enabling practice environment.